2019
DOI: 10.1186/s12885-019-5356-3
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis in penile corpus cavernosum from esophageal squamous carcinoma after curative resection: a case report

Abstract: Background Metastasis in penile corpus cavernosum from esophageal squamous carcinoma is a rare but fatal disease, which was reported in cases without series studies. Case presentation An 84-year-old male smoker, who had a history of curative resection of esophageal squamous carcinoma 12 months before, presented with aggressive dysuria and penis pain for 1 month. Ultrasonic guided biopsy diagnosed metastatic squamous carcinoma from the primary in the esophagus. The accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Except for few cases, survival does not exceed 2 years after diagnosis of penile metastatic disease and most patients die between 3 and 12 months after diagnosis. 1,2 Our patient is the fourth reported case of penile metastasis from pancreatic adenocarcinoma. The first one was reported in 1971 by Weitzner, 5 who described a squamous cell carcinoma of the pancreas with multiple organ metastasis in autoptic findings.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Except for few cases, survival does not exceed 2 years after diagnosis of penile metastatic disease and most patients die between 3 and 12 months after diagnosis. 1,2 Our patient is the fourth reported case of penile metastasis from pancreatic adenocarcinoma. The first one was reported in 1971 by Weitzner, 5 who described a squamous cell carcinoma of the pancreas with multiple organ metastasis in autoptic findings.…”
Section: Discussionmentioning
confidence: 77%
“…The remaining 5% is equally shared between bone and skin malignancies. 2,3 The suggested spreading mechanism to the penis is probably through the hematologic route, via arterial or retrograde venous supply, but also a lymphovascular and direct spread from the surrounding organs has been proposed. Authors reported neoplastic thrombi in a high proportion of metastases from colonrectum and genitourinary tract.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results are consistent with the findings of previous studies that have investigated penile metastasis from other primary sites. Song et al [ 14 ] emphasised that the time to metastasis occurrence was negatively correlated with the prognosis in penile metastasis from oesophageal squamous carcinoma. According to Wen et al [ 15 ], lymph node metastasis may have a negative correlation with the prognosis.…”
Section: Discussionmentioning
confidence: 99%